FORMING OF PROFESSIONALLY CREATIVE COMPETENCE OF PROSPECTIVE AGRARIAN MANAGERS BY FACILITIES OF DIGITAL TECHNOLOGIES - Klochko, Oksana; Nagayev, Viktor; Kovalenko, Oksana; Fedorets, Vasyl (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The component structure of professionally creative competence is analyzed in the system of professional preparation of the future agrarian managers. Didactics facilities of digital technologies are grounded in the context of forming of professionally-creative competence of the future agrarian managers. A pedagogical model of management of future agrarian managers’ educational-creative activity by facilities of the digital technologies is worked out. In the proposed pedagogical model, the object of management is the educational and creative activity of students in the conditions of SMART technologies, which turns the existing potential of a future specialist into a qualitative result - the formation of the experience of creative activity of the agricultural manager in the system of his professional competence. The technological stages of management of the future agrarian managers’ educational-creative activity by facilities of digital technologies are justified. Efficiency of the agrarian managers’ professional preparation with the use of pedagogical model of management of future agrarian managers’ educational-creative activity by facilities of the digital technologies as compared with the traditional system of teaching is defined. The results of the study determined the directions of further scientific and pedagogical research: the development of computer-oriented methodological systems of STEM-education and SMART-complexes of educational disciplines in digital pedagogy.